2012
DOI: 10.1107/s0907444912022640
|View full text |Cite
|
Sign up to set email alerts
|

Structural reorganization of the bacterial cell-division protein FtsZ fromStaphylococcus aureus

Abstract: FtsZ is a key molecule in bacterial cell division. In the presence of GTP, it polymerizes into tubulin-like protofilaments by head-to-tail association. Protofilaments of FtsZ seem to adopt a straight or a curved conformation in relation to the bound nucleotide. However, although several bacterial and archaeal FtsZ structures have been determined, all of the structures reported previously are considered to have a curved conformation. In this study, structures of FtsZ from Staphylococcus aureus (SaFtsZ) were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
207
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(232 citation statements)
references
References 58 publications
(89 reference statements)
15
207
1
Order By: Relevance
“…Thus, the Asp280-Arg20 salt bridge is critical for complex stability. (10) showed that the presence of MciZ would completely prevent the association of FtsZ monomers (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Asp280-Arg20 salt bridge is critical for complex stability. (10) showed that the presence of MciZ would completely prevent the association of FtsZ monomers (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…FtsZ and tubulin share several essential properties: their assembly is cooperative, stimulated by GTP, and leads to GTP hydrolysis; they form dynamic polymers whose turnover is dependent on nucleotide hydrolysis (8); they use essentially the same bond for polymer formation (9); and recent evidence indicates that they undergo similar allosteric transitions upon polymerization (10,11). Not surprisingly, however, the functional specialization of these proteins led to some significant differences between them, the most prominent being that FtsZ exists as single protofilaments, whereas tubulin always adopts a multifilament tubular structure.…”
mentioning
confidence: 99%
“…Huecas and Andreu (30) studied the effect of nucleotide in Methanococcus janaschii FtsZ and found that apo FtsZ assembled approximately the same as the GTP-bound and that addition of GDP caused rapid disassembly. Staphylococcus aureus FtsZ typically crystallizes in the form of assembled pfs (31,32), with GDP in the nucleotide pocket. The protein was purified without any nucleotide, so this implies that the GDP remained tightly bound during purification and crystallization.…”
Section: Discussionmentioning
confidence: 99%
“…All of these structures were very similar, irrespective of the bound nucleotide, and the slight differences observed seemed to be related to interspecies differences (22). Recently, however, Staphylococcus aureus FtsZ (SaFtsZ) 3 has been shown to have a markedly different structure by sliding/rotation between two subdomains with concomitant conformational change of the T7 loop (23). This structure seemed to be related to the polymerization state; the T7 loop of the "upper" subunit in SaFtsZ was inserted more deeply into the nucleotide-binding pocket of the "lower" subunit than any other structure determined to date.…”
mentioning
confidence: 99%
“…This structure seemed to be related to the polymerization state; the T7 loop of the "upper" subunit in SaFtsZ was inserted more deeply into the nucleotide-binding pocket of the "lower" subunit than any other structure determined to date. Therefore, the SaFtsZ structure has been interpreted as representing a straight protofilament conformation, whereas other structures are curved (and relaxed) conformations (23). This view is reinforced by the observation that SaFtsZ bound with PC190723, which inhibits GTPase activity by stabilizing the polymer formation (24), has the same conformation (23,25,26).…”
mentioning
confidence: 99%